The Association of Statin Use with Age-Related Macular Degeneration Progression The Age-Related Eye Disease Study 2 Report Number 9 - Al-Holou, Shaza N. (Ophthalmology, 2015)
OBJECTIVE/PURPOSE: To evaluate the association of statin use with progression of age-related macular degeneration (AMD). DESIGN: Preplanned, prospective cohort study within a controlled clinical trial of oral supplementation for age-related eye diseases. SUBJECTS: Age-Related Eye Disease Study 2 participants, aged 50 to 85 years. METHODS: Factors, including age, gender, smoking status, aspirin use, and history of diabetes, hypertension, heart disease, angina, and stroke, all known to be associated with statin use, were included in a logistic regression model to estimate propensity scores for each participant. Age-adjusted proportional hazards regression models, with and without propensity score matching, were performed to evaluate the association of statin use with progression to late AMD. Analyses were also performed adjusting for the competing risk of death. MAIN OUTCOME MEASURES: Baseline and annual stereoscopic fundus photographs were assessed centrally by masked graders for the development of late AMD, either neovascular AMD or geographic atrophy (GA). RESULTS: Of the 3791 participants (2462 with bilateral large drusen and 1329 with unilateral late AMD at baseline), 1659 (43.8%) were statin users. The overall analysis, with no matching of propensity scores and no adjustment for death as a competing risk, showed that statin use was not associated with progression to late AMD (hazard ratios [HR] of 1.08, 95% confidence intervals [CI] of 0.83–1.41, P=0.56). When matched for propensity scores and adjusted for death as a competing risk, the result was not statistically significant with HR: 0.81, 95% CI: 0.55–1.20, P=0.29. Further subgroup analyses of persons with or without late AMD at baseline to the various components of late AMD (neovascular, central geographic atrophy, or any geographic atrophy) also showed no statistically significant association of statin use with progression to AMD. CONCLUSIONS: Statin use was not statistically significantly associated with the progression to late AMD in the AREDS2 participants, and these findings are consistent with the findings in the majority of previous studies. Statins have been demonstrated to reduce the risks of cardiovascular disease, but our data do not provide evidence of a beneficial effect on slowing AMD progression.